ANALISIS PREFERENSI KONSUMEN TERHADAP RUMAH HUNIAN DI KOTA MATARAM - Ahdari Muharrar; Ketut Budastra; Suryawan Murtiadi (Media Bina Ilmiah, 2023)
Housing as a living environment equipped with environmental infrastructure and facilities as well as a house as a building where humans live and lead a life. Housing is also a place where the technical, physical, social, economic and cultural aspects of an individual take place. Communities as consumers who want to find a place to live often experience difficulties due to a lack of references and limited knowledge. Developers as housing developers often get less response from consumers which results in losses due to miscalculations and limited knowledge. The purpose of this study is to examine a number of factors that are important elements in a housing. Variables are created in the form of attributes and attribute levels. The research was conducted using a questionnaire and then processed by conjoint method analysis with the SPSS program. There are 5 attributes and 13 levels of attributes that were tested during the research. The first is the physical building with attribute levels of Type I, Type II, and Type III. Both residential locations with downtown and suburban attribute levels. The third is the professionalism and experience of the developer with the attribute level of credibility, law abiding and commitment. The four housing support facilities with attribute levels of green open space (RTH), club house, and security. The five promotional media are at the attribute level of print and electronic media. The results showed that housing with club house facilities, Type II, which is located in the city center, which is marketed via electronic media, by law-abiding developers is the most ideal housing planning combination. In commercial housing the element that is most considered is the availability of supporting facilities, while in subsidized housing the element that is most considered is the physical building including the area of the building and land, price, and the appearance of the building.